PERMAINAN TRADISIONAL CONGKLAK UNTUK MENGEMBANGKAN ASPEK PERKEMBANGAN ANAK USIA 5-6 TAHUN DI PAUD TAMAN PENA - Armi Harbiyah; Marmawi R; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the traditional game of congklak in developing aspects of the development of children aged 5-6 years at PAUD Taman Pena, Kuala Dua Village, Kubu Raya Regency. The research method used is descriptive method in the form of qualitative research. Sources of data in the study of children aged 5-6 years. Data collection techniques used are observation, interviews, and documentation. The results showed that: 1. The traditional game of congklak in developing aspects of moral values contained the ability to behave well, such as children being able to behave honestly, sportsmanly, and obediently, 2. Congklak traditional game in developing the physical aspects contained in fine motor skills such as grip strength and flexibility of the fingers, 3. Congklak traditional games in developing cognitive aspects include the ability to recognize numbers, count, distinguish between many and few, 4. Congklak traditional games in developing language aspects which include the ability to understand language such as understanding rules and expressing language such as communicating orally, 5. Games traditional congklak in developing social emotional aspects there are prosocial behavior abilities such as respecting rights/opinions, expressing emotions according to existing conditions, and being patient 6. Traditional congklak games in developing artistic aspects have the ability to enjoy various strains of songs or sounds such as singing. Thus, the traditional game of congklak has potential as a means in the learning process because it can develop aspects of the development of children aged 5-6 years at PAUD Taman Pena, Kuala Dua Village, Kubu Raya Regency.